Association Between Vitamin A Supplementation and Mortality Among Patients with Ebola Virus Disease: An International Multisite Cohort Study. Issue Volume 34:Issue s1(2019) (May 2019) - Aluisio, Adam; Yam, Derrick; Peters, Jillian L.; Cho, Daniel K.; Perera, Shiromi M.; Kennedy, Stephen B.; Sahr, Foday; Garbern, Stephanie; Liu, Tao; Levine, Adam C.
Abstract : Introduction: Micronutrient supplementation is recommended in Ebola Virus Disease (EVD). However, there is limited data on its therapeutic impacts. This study evaluated the association between vitamin A supplementation and mortality outcomes in EVD patients. Methods: This retrospective cohort study accrued patients with EVD admitted to five International Medical Corps run Ebola Treatment Units (ETU) in two countries from 2014-2015. Protocolized treatments with antimicrobials and micronutrients were used at all ETUs. However, due to resource limitations and care variations, only a subset of patients received vitamin A. Standardized data on demographics, clinical characteristics, malaria status, and Ebola virus RT-PCR cycle threshold (CT) values were collected. The outcome of interest was mortality compared between cases treated with 200, 000 International Units of vitamin A on care days one and two and those not. Propensity scores (PS) based on the first 48-hours of care were derived using the covariates of age, duration of ETU function, malaria status, CT values, symptoms of confusion, hemorrhage, diarrhea, dysphagia, and dyspnea. Treated and non-treated cases were matched 1:1 based on nearest neighbors with replacement. Covariate balance met predefined thresholds. Mortality proportions between cases treated and untreated with vitamin A were compared using generalized estimating equations to calculate relative risks (RR) with associated 95% confidence intervals (CI). Results: There were 424 cases analyzed, with 330 (77.8%) being vitamin A-treated cases. The mean age was 30.5 years and 57.0% were female. The most common symptoms were diarrhea (86%), anorexia (81%), and vomiting (77%). Mortality proportions among cases untreated and treated with vitamin A were 71.9% and 55.0%, respectively. In a propensity-matched analysis, mortality was significantly lower among cases receiving vitamin A (RR = 0.77 95%; CI:0.59-0.99; p = 0.041). Discussion: Early vitamin A supplementation was associated with reduced mortality in EVD patients and should be provided routinely during future epidemics.